Pemberdayaan Masyarakat Melalui Badan Usaha Milik Desa sebagai Sentra Produk Pangan Berbasis Jagung dan Mete - Zainal Abidin; Titik Sri Harini; Hironnymus Jati; Lewi Jutomo; Gabriella Dhyang Dyah Puspitaningtyas; Sarniyati Wini Wanno; Matris Awardi Tamelab; Jefrianus Toy Sanan; Meki Jefry Beti (Yumary: Jurnal Pengabdian kepada Masyarakat, 2022)
Purpose: To increase the knowledge and skills of partners in corn and cashew-based food processing and knowledge of distribution permits, improve the quality and selling value of products using Appropriate Technology, organize the organization and management of food processing, and assess the role of Village-Owned Enterprise (VOE) in community empowerment. Method: Solving partner problems are replacing manual equipment with appropriate technology, counseling, training, assistance in processing corn and cashews, improving organization and management, and assisting in managing distribution permits. The target of the activity is the partner farmer group of the food processing business unit of the Sillu Raya VOE. Results: Achieved were an increase in knowledge about the importance and management of distribution permits, more effective and efficient processed food production processes, mastery of appropriate technology, halal-certified and labeled products, improved structure and management of food processing business units, Sillu Raya VOE have not play an effective role in empowering the community's economy. The knowledge and skills of partners increase, partners master appropriate technology and the selling value of marning corn and various processed cashew nuts increases. Assistance will be by seeking food safety education with resource persons from the Food and Drug Monitoring Agency of East Nusa Tenggara as a condition of obtaining a distribution permit for market expansion. Contribution: To increasing the knowledge and skills of the community so that they are independent in food processing in order to increase the added value of the products produced.